Cortical laminar necrosis detected by diffusion-weighted imaging in a dog suspected of having hypoglycemic encephalopathy - HORI, Ai (J Vet Med Sci, 2020)
We describe a 5-year-old castrated male dog suspected hypoglycemic encephalopathy that was evaluated by using diffusion-weighted imaging (DWI). The dog experienced hypoglycemia after prolonged generalized and continued partial seizures. In the acute phase, DWI showed hyperintensity in the left temporal lobe. After about a month, DWI maintained hyperintensity, and left middle cerebral artery dilation was noted on magnetic resonance angiography (MRA). In the chronic phase, the left temporal lobe lesion was replaced by cerebrospinal fluid. In humans, it was reported that cortical laminar necrosis (CLN) with hypoglycemic encephalopathy presents hyperintensity in the cerebral cortex on DWI and increased vascularity of the middle cerebral artery branches on MRA. In conclusion, DWI has detected CLN in a dog suspected hypoglycemic encephalopathy.